A water-based inorganic zinc-rich primer that can be applied in a low-temperature environment and a preparation method thereof
By adopting specific A and B components formulas in aqueous inorganic zinc-rich primer, the problems of construction difficulties and porous coatings in low-temperature environments are solved, and the effects of long construction window period, dense coating, excellent corrosion resistance and high temperature resistance are achieved.
Patent Information
- Application Number
- CN202510073448.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing water-based inorganic zinc-rich primer is difficult to construct in low-temperature environments, has a short construction time, a slow drying and curing speed, and the coating has microporous problems, which affects subsequent coating construction.
A water-based inorganic zinc-rich primer consisting of two components A and B is used. Component A includes aqueous potassium silicate solution and carboxylated modified cellulose nanocrystal predispersion. Component B includes modified zinc powder, modified conductive carbon black, composite low-temperature quick-drying catalyst and phosphorus iron powder. Through the combination of these components, rapid construction and efficient curing are achieved in low-temperature environments.
The water-based inorganic zinc-rich primer is realized for low-temperature environments. The construction window period is long, the coating is dense and has no micropores, excellent corrosion resistance, and good high temperature resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a water-based inorganic zinc-rich primer which can be constructed in a low-temperature environment and a preparation method thereof, belonging to the technical field of coatings. Background Art
[0002] Waterborne inorganic zinc-rich primer is a two-component waterborne room temperature curing anticorrosive coating with high modulus silicate aqueous solution as binder and ultrafine high-activity zinc powder as main anti-rust pigment. The silicate aqueous solution mainly refers to sodium silicate, potassium silicate, lithium silicate, etc. The usual chemical formula is: M2·mSiO2·nH2O, where M is Na + , K + , Li + etc., m and n are the molar numbers of the three components M2O, SiO2 and H2O.
[0003] The reaction mechanism of water-based inorganic zinc-rich primer: the active silica in the silicate aqueous solution reacts chemically with the active zinc powder in the paint film and the active iron atoms on the surface of the sandblasted steel structure to form a zinc ion-silicate ion-iron ion complex structure. The paint film is attached to the surface of the steel structure through chemical bonds and has excellent adhesion. Even after being bumped, the paint film will not peel or fall off in a large area, but only pits will appear at the bumps, and the paint film will protect the base layer on the pits, making it not easy to rust.
[0004] During the drying process of the paint film of the water-based inorganic zinc-rich primer, the zinc powder and the steel base are connected by the silicate structure to form a whole. When the paint is applied to the surface of the steel structure substrate, the zinc powder particles and the steel substrate and the zinc powder maintain direct metal contact, and the paint film and the substrate can be tightly combined through the reaction of the silicon-oxygen bond with the zinc powder and the substrate. In this state, if water invades the inside of the paint film, a battery composed of zinc powder and iron is formed. Since the potential of zinc is lower than that of iron, the zinc powder acts as an anode to protect the iron as a cathode, so that the steel structure substrate will not rust. The zinc powder will rust in this process and produce white rust, which is the so-called cathodic protection effect.
[0005] After the paint film is completely dry, the zinc powder in the paint film will continue to react chemically with H2O, CO2, O2, SO2 and other substances in the air, which is the so-called post-curing. The post-curing process will generate corrosion products such as zinc oxide, zinc hydroxide, basic zinc carbonate, zinc sulfate, etc. The post-curing process lasts for a long time. As the reaction process continues, these corrosion products gradually accumulate in the gaps between the zinc powder in the paint film, improving the density and cohesive strength of the paint film and enhancing the anti-seepage shielding performance of the paint film. At the same time, the corrosion filler will also reduce the conductivity of the paint film, reduce the current intensity of the electrochemical reaction, and thus greatly reduce the consumption rate of zinc powder, thereby greatly enhancing the durability of the paint film. This reaction process usually lasts for several weeks to several months, or even longer.
[0006] In general, waterborne inorganic zinc-rich primers have excellent properties such as zero VOC, ultra-long durability, high temperature resistance, cathodic protection, solvent resistance, and wear resistance. However, in actual use, waterborne inorganic zinc-rich primers also have the following outstanding problems: (1) The construction time of waterborne inorganic zinc-rich primers is too short. When preparing the paint, a large amount of zinc powder is added. Zinc is a heavy metal. After the paint is prepared, it is easy to precipitate and form cakes, making the paint ineffective. Construction within a short time is required, which brings difficulties to the high-quality and high-efficiency construction of the paint. (2) The paint film has a slow curing rate and has relatively high requirements for the construction environment. It cannot be sprayed at a lower temperature. Generally, the temperature must not be lower than 5°C and the relative humidity must not exceed 80%. (3) It is microporous and has poor shielding properties. The zinc content in general water-based inorganic zinc-rich primers is as high as 70~80%, which has far exceeded the critical volume concentration (CPVC) of fillers. At this time, the amount of inorganic silicate binder is not enough to fill the gaps between zinc powder particles, making the coating porous. If other topcoats are applied on the primer, the probability of bubbles in the topcoat will increase. Although the post-curing process can gradually accumulate corrosion products in the gaps between zinc powder in the paint film, improving the density and cohesive strength of the paint film and enhancing the anti-seepage shielding performance of the paint film, this process usually takes several weeks to several months, or even longer. Obviously, it is difficult to wait for several weeks to several months to wait for the post-curing to be completed and there is no microscopic porosity problem before applying the topcoat. From the above discussion, it can be seen that the current water-based inorganic zinc-rich primer has three major problems: short construction time caused by too fast zinc powder sedimentation, slow drying rate in low temperature environment, and poor construction, and microscopic porosity of the coating affecting subsequent coating construction.
[0007] Chinese patent CN102775828A discloses a slow-release drying water-based inorganic zinc-rich coating, which is composed of a main agent and a curing agent, wherein the weight ratio of the main agent to the curing agent is 100:30-50. The slow-release drying water-based inorganic zinc-rich coating of the present invention is prepared by using a slow-release drying modifier, and then combining zinc powder, functional fillers, etc.
[0008] Zinc coating has changed the harsh conditions of traditional water-based inorganic zinc-rich coatings, which are that the wind speed cannot be greater than level 3 and the substrate temperature cannot be higher than 30°C during outdoor construction. It can be applied to the surface of sandblasted steel substrates under outdoor wind speed level 5 and temperature 50°C. The water-based inorganic zinc-rich primer prepared by this patent has a short construction time, slow drying and curing speed, and the resulting paint film is resistant to salt spray.
[0009] The performance is also relatively poor.
[0010] Chinese patent CN104974626A discloses a two-component water-based inorganic zinc-rich primer and its preparation method and application. The preparation method of the coating comprises the steps of: placing a water-soluble potassium silicate solution in a container, slowly adding a certain amount of silica sol and deionized water, and then slowly dripping a silane coupling agent into the solution, and keeping the material stirred. After a certain period of reaction, the silicone-acrylic emulsion is added to the completely reacted mixed solution under extremely low-speed stirring conditions, and the mixture is filtered and packaged after continuous stirring for a certain period of time. Component A of the water-based inorganic zinc-rich primer is obtained. High-purity metallic zinc powder and a small amount of additives are packaged according to specifications to obtain a water-based inorganic zinc-rich component B. The inorganic zinc-rich primer obtained by this patent has a slow drying and curing speed and a relatively short construction time. In addition, due to the addition of organic components, the high temperature resistance of the paint film will also deteriorate.
[0011] From the above, we can see that the current water-based inorganic zinc-rich primer has three major problems: short construction time due to too fast zinc powder sedimentation, slow drying rate in low-temperature environment and inability to construct, and microscopic porosity of the coating affecting subsequent coating construction. Therefore, it is of great practical application value to develop a water-based inorganic zinc-rich primer that can be constructed in a low-temperature environment with a long construction window period and a dense coating without microscopic pores. Summary of the invention
[0012] In view of the deficiencies in the above-mentioned prior art, the present invention provides a water-based inorganic zinc-rich primer that can be constructed in a low-temperature environment and a preparation method thereof, to achieve the following invention objectives: to prepare a water-based inorganic zinc-rich primer that can be constructed in a low-temperature environment, has a long construction window period, has a dense coating without microscopic fine pores and has excellent anti-corrosion performance.
[0013] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0014] A water-based inorganic zinc-rich primer that can be applied in a low-temperature environment and a preparation method thereof. The water-based inorganic zinc-rich primer that can be applied in a low-temperature environment consists of two components, A and B. During application, the components A and B are evenly mixed in a mass ratio of 3 to 4:7 and then used.
[0015] The specific formula of the component A is, in parts by weight:
[0016] 130-180 parts of potassium silicate aqueous solution,
[0017] 10-25 parts of carboxylated modified cellulose nanocrystal pre-dispersion liquid,
[0018] 20~55 parts of deionized water;
[0019] In the potassium silicate aqueous solution, the mass concentration of potassium silicate is 20-30wt%, and the modulus of potassium silicate is 2-3.5;
[0020] The preparation method of the carboxylated modified cellulose nanocrystal pre-dispersion liquid is as follows: after mixing the carboxylated modified cellulose nanocrystal and deionized water at a mass ratio of 17-29:130, using a high-speed disperser to vigorously disperse the mixture at a speed of 8000-12000 rpm for 5-9 hours to obtain a gel-like viscous liquid, which is the carboxylated modified cellulose nanocrystal pre-dispersion liquid;
[0021] The carboxylated modified cellulose nanocrystals have a diameter of 4-10 nm, a length of 100-500 nm, and a surface carboxyl content of 0.4-0.7 mmol / g;
[0022] The specific formula of the B component is, in parts by weight:
[0023] Modified zinc powder 80~130 parts,
[0024] Modified conductive carbon black 10~25 parts,
[0025] 3~8 parts of composite low temperature quick drying catalyst,
[0026] 20~45 parts of ferrophosphorus powder;
[0027] The composite low-temperature quick-drying catalyst has a preparation method comprising: mixing 4-aminobutyric acid, pyromellitic acid, and mellitic acid in a mass ratio of 1-4:30-60:5-9, drying in an oven at 40-60° C. for 13-20 hours, and then putting the mixture into a dry ball mill for ball milling to a particle size of 0.5-3 μm, and then discharging the mixture to obtain a powdered composite low-temperature quick-drying catalyst;
[0028] The particle size of the ferrophosphorus powder is 600-800 mesh;
[0029] The following are further improvements to the above technical solution:
[0030] Step 1: Preparation of modified zinc powder
[0031] The zinc powder and acetone are placed in a high-speed dispersion kettle, and the dispersion rate is controlled at 6000-9500 rpm. After strong dispersion for 3-7 hours, the dispersion rate is reduced to 2000-3500 rpm, ethyl silicate is added to the kettle, and then deionized water is added dropwise at a rate of 0.01-0.4 g / min. After the addition is completed, the dispersion reaction is continued for 2-5 hours, and then hexamethyldisilazane is added. After the dispersion reaction is continued for 1-3.5 hours, centrifugation is performed, and the separated solid is washed with anhydrous ethanol for 3-4 times, and then placed in a 50-60° C. oven. After drying for 5-10 hours, a modified zinc powder is obtained;
[0032] The zinc powder is spherical zinc powder with a particle size of 600-1000 mesh;
[0033] The mass ratio of the zinc powder, acetone, ethyl silicate, deionized water and hexamethyldisilazane is 40-75:130-200:5-15:0.5-1.1:2-5.
[0034] Step 2: Preparation of modified conductive carbon black
[0035] Conductive carbon black and deionized water are placed in a high-speed dispersion kettle, and the dispersion rate is controlled at 7000-10000 rpm. After strong dispersion for 5-9 hours, the dispersion rate is reduced to 2000-3000 rpm, and then the temperature is raised and kept constant at 40-60°C. Then trifluoroacetic acid and sulfuric acid are added, and the reaction is dispersed at a constant temperature for 4-7 hours, and then centrifuged. The separated solid is washed with deionized water for 3-5 times, and dried at 80-90°C for 4-9 hours to obtain a surface-etched conductive carbon black. Then, the surface-etched conductive carbon black and acetone are placed in a high-speed dispersion kettle, and the dispersion rate is controlled at 8000-10000 rpm. After intensive dispersion for 6-10 hours, the dispersion rate is reduced to 2000-3500 rpm, and then 3-aminopropyltriethoxysilane is added. After the dispersion reaction is continued for 5-8 hours, the modified conductive carbon black is obtained by centrifugation. The separated solid is washed with deionized water for 2-4 times, and dried at 60-90°C for 4-8 hours to obtain the modified conductive carbon black.
[0036] The particle size of the conductive carbon black is 20-30 nm, and the specific surface area is 800-1000 m 2 / g, oil absorption value is 200~300mL / 100g, and resistance is 0.1~0.5Ω·m;
[0037] The mass ratio of the conductive carbon black, deionized water, trifluoroacetic acid and sulfuric acid is 20-60:100-220:5-25:15-30;
[0038] The mass ratio of the conductive carbon black, acetone and 3-aminopropyltriethoxysilane for surface etching is 10-50:90-180:5-11.
[0039] Step 3: Preparation of component A
[0040] According to the specific formula of component A of the water-based inorganic zinc-rich primer that can be constructed in a low-temperature environment, in parts by weight, corresponding parts by weight of potassium silicate aqueous solution, carboxyl modified cellulose nanocrystal pre-dispersion liquid, and deionized water are put into a high-speed dispersing kettle, and the dispersion rate is controlled at 5000-8000 rpm. After intensive dispersion for 1.5-3 hours, the material is discharged to obtain component A.
[0041] Step 4: Preparation of component B
[0042] According to the specific formula of component B of the water-based inorganic zinc-rich primer that can be constructed in a low-temperature environment, in parts by weight, corresponding parts by weight of modified zinc powder, modified conductive carbon black, composite low-temperature quick-drying catalyst, and ferrophosphorus powder are put into a high-speed mixer, and the stirring rate is controlled at 130-200 rpm. After stirring and mixing for 1-2.5 hours, the material is discharged to obtain component B.
[0043] Compared with the prior art, the present invention achieves the following beneficial effects:
[0044] 1. The present invention uses ethyl silicate and hexamethyldisilazane to coat and modify zinc powder to a certain extent. The coated and modified zinc powder has a certain number of active silanol groups on its surface, which can accelerate the reaction rate of zinc powder and potassium silicate and shorten the surface drying and actual drying time. In addition, after coating the active silanol groups, there is an adsorption and competition relationship of hydrogen bonds between zinc powder particles and between zinc powder and water molecules. In this way, zinc powder particles are not easy to aggregate and settle due to the hydrogen bond competition of water molecules, thereby extending the construction window period of the primer. Moreover, after the surface of the zinc powder is modified, the crosslinking density of the paint film is effectively increased, the compactness of the paint film is increased, and the corrosion resistance of the paint film is increased.
[0045] 2. The present invention uses trifluoroacetic acid and sulfuric acid to perform surface etching on the conductive carbon black. After the surface etching, the surface polarity of the conductive carbon black is enhanced, and the surface will have more polar groups such as carboxyl and hydroxyl groups. Then these groups react with 3-aminopropyltriethoxysilane. After the reaction is completed, the surface of the conductive carbon black is covered with aminopropyl functional groups. The aminopropyl group has very good hydrophilicity, which will promote the conductive carbon black to achieve rapid and uniform dispersion after the two components of the water-based inorganic zinc-rich primer are mixed, avoid the agglomeration and sedimentation of the conductive carbon black, and then ensure the uniformity of the conductive carbon black in the paint film. The conductive carbon black is evenly dispersed in the cured paint film. First, the particle size of the conductive carbon black is at the nanometer level, which can effectively fill the micron-sized zinc powder and micron-sized phosphorus iron. The first is the pores formed between the powders. The second is that the conductive carbon black has very excellent conductivity and can form an effective conductive network between the zinc powder particles, between the zinc powder and the ferrophosphorus powder particles, and between the ferrophosphorus powder particles. This can reduce the amount of zinc powder and increase the amount of ferrophosphorus powder with poor conductivity. This better conductive network can more effectively ensure that the zinc powder can play a cathodic protection role in all local areas of the entire paint film and areas lacking zinc powder. This greatly reduces the amount of zinc powder used and effectively solves the problem of rapid sedimentation caused by excessive zinc powder. It can also improve the flexibility, corrosion resistance and high temperature resistance of the paint film, because carbon black itself is an inorganic non-metallic material with very excellent high temperature resistance.
[0046] 3. The low-temperature quick-drying catalyst composed of 4-aminobutyric acid, pyromellitic acid and mellitic acid added to component B of the present invention can effectively improve the drying and curing speed of the paint film. This is mainly because the three substances contain relatively active carboxyl groups. These two groups can effectively induce and catalyze the cross-linking and curing reaction between silanol and zinc powder, thereby effectively improving the low-temperature drying rate of the paint film, so that the water-based inorganic zinc-rich primer can better meet the stringent requirements of construction under low temperature conditions;
[0047] 4. The carboxylated modified cellulose nanocrystal pre-dispersion prepared by the present invention has very good thixotropic thickening performance, can effectively inhibit the sedimentation of zinc powder and ferrophosphorus powder, and prolong the construction window period. In addition, the carboxylated modified cellulose nanocrystals also have more terminal carboxyl groups, and can catalyze the cross-linking and curing reaction between silanol and zinc powder, shorten the surface drying and actual drying time, increase the cross-linking density of the paint film, and improve the salt spray resistance to a certain extent. The polarity of the carboxylated modified cellulose nanocrystals is very large, and can effectively bond to polar surfaces such as metals to improve the adhesion of the paint film, but the carboxylated modified cellulose nanocrystals have a certain negative impact on the high temperature resistance of the paint film;
[0048] 5. The water-based inorganic zinc-rich primer obtained by the present invention can be constructed in a low-temperature environment. The construction time after the components A and B are mixed is 83 to 93 minutes, the surface drying time at 5°C and a humidity of 50% is 5 to 6 minutes, and the actual drying time is 35 to 42 minutes. The surface drying time at 20°C and a humidity of 50% is 2 to 4 minutes, and the actual drying time is 23 to 26 minutes. The obtained paint film has a flexibility of 1 mm, an adhesion of 12 to 15 MPa, a neutral salt spray resistance of 5754 to 5986 hours, and a high temperature resistance of 253 to 260 hours. DETAILED DESCRIPTION
[0049] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0050] Example 1: A method for preparing a water-based inorganic zinc-rich primer that can be applied in a low temperature environment
[0051] Step 1: Preparation of modified zinc powder
[0052] The zinc powder and acetone were placed in a high-speed dispersion kettle, and the dispersion rate was controlled at 8500 rpm. After intensive dispersion for 6 hours, the dispersion rate was reduced to 3000 rpm, ethyl silicate was added to the kettle, and then deionized water was added dropwise at a rate of 0.3 g / min. After the addition was completed, the dispersion reaction was continued for 4 hours, and then hexamethyldisilazane was added. After the dispersion reaction was continued for 2 hours, centrifugation was performed, and the separated solid was washed with anhydrous ethanol for 3 times, and then placed in a 56°C oven. After drying for 8 hours, modified zinc powder was obtained;
[0053] The zinc powder is spherical zinc powder with a particle size of 900 meshes;
[0054] The mass ratio of the zinc powder, acetone, ethyl silicate, deionized water and hexamethyldisilazane is 60:170:11:0.8:4.
[0055] Step 2: Preparation of modified conductive carbon black
[0056] Conductive carbon black and deionized water are placed in a high-speed dispersion kettle, and the dispersion rate is controlled at 9000 rpm. After 6 hours of strong dispersion, the dispersion rate is reduced to 2600 rpm, and then the temperature is increased and kept constant at 55°C, and then trifluoroacetic acid and sulfuric acid are added. After the constant temperature dispersion reaction is performed for 6 hours, centrifugation is performed, and the separated solid is washed with deionized water for 4 times, and dried at 87°C for 6 hours to obtain surface-etched conductive carbon black. Then, the surface-etched conductive carbon black and acetone are placed in a high-speed dispersion kettle, and the dispersion rate is controlled at 8600 rpm. After 9 hours of strong dispersion, the dispersion rate is reduced to 3000 rpm, and then 3-aminopropyltriethoxysilane is added. After the dispersion reaction is continued for 7 hours, centrifugation is performed, and the separated solid is washed with deionized water for 3 times, and dried at 80°C for 7 hours to obtain modified conductive carbon black.
[0057] The particle size of the conductive carbon black is 26 nm and the specific surface area is 950 m 2 / g, oil absorption value is 240mL / 100g, and resistance is 0.2Ω·m;
[0058] The mass ratio of the conductive carbon black, deionized water, trifluoroacetic acid and sulfuric acid is 50:160:15:20;
[0059] The mass ratio of the conductive carbon black, acetone and 3-aminopropyltriethoxysilane for surface etching is 40:130:7.
[0060] Step 3: Preparation of component A
[0061] The specific formula of the component A is, in parts by weight:
[0062] 160 parts of potassium silicate aqueous solution,
[0063] 20 parts of carboxylated modified cellulose nanocrystal pre-dispersion liquid,
[0064] 40 parts of deionized water;
[0065] In the potassium silicate aqueous solution, the mass concentration of potassium silicate is 24wt%, and the modulus of potassium silicate is 3;
[0066] The preparation method of the carboxylated modified cellulose nanocrystal pre-dispersion liquid is as follows: after mixing the carboxylated modified cellulose nanocrystal and deionized water at a mass ratio of 20:130, using a high-speed disperser to vigorously disperse for 8 hours at a speed of 9000 rpm to obtain a gel-like viscous liquid, which is the carboxylated modified cellulose nanocrystal pre-dispersion liquid;
[0067] The carboxylated modified cellulose nanocrystals have a diameter of 6 nm, a length of 400 nm, and a surface carboxyl content of 0.6 mmol / g;
[0068] According to the specific formula of component A of the water-based inorganic zinc-rich primer that can be constructed in a low-temperature environment, in parts by weight, corresponding parts by weight of potassium silicate aqueous solution, carboxyl modified cellulose nanocrystal pre-dispersion liquid, and deionized water are put into a high-speed dispersing kettle, and the dispersion rate is controlled at 7000 rpm. After intensive dispersion for 2 hours, the material is discharged to obtain component A.
[0069] Step 4: Preparation of component B
[0070] The specific formula of the B component is, in parts by weight:
[0071] 100 parts of modified zinc powder,
[0072] 20 parts of modified conductive carbon black,
[0073] 5 parts of composite low temperature quick drying catalyst,
[0074] 40 parts of ferrophosphorus powder;
[0075] The composite low-temperature quick-drying catalyst is prepared by mixing 4-aminobutyric acid, pyromellitic acid and mellitic acid in a mass ratio of 3:45:7, drying in an oven at 55°C for 17 hours, and then putting the mixture into a dry ball mill for ball milling to a particle size of 2 μm to obtain a powdered composite low-temperature quick-drying catalyst.
[0076] The particle size of the ferrophosphorus powder is 700 mesh;
[0077] According to the specific formula of component B of the water-based inorganic zinc-rich primer that can be constructed in a low-temperature environment, in parts by weight, corresponding parts by weight of modified zinc powder, modified conductive carbon black, composite low-temperature quick-drying catalyst, and ferrophosphorus powder are put into a high-speed mixer, and the stirring rate is controlled at 180 rpm. After stirring and mixing for 2 hours, the material is discharged to obtain component B.
[0078] Example 2: A method for preparing a water-based inorganic zinc-rich primer that can be applied in a low temperature environment
[0079] Step 1: Preparation of modified zinc powder
[0080] The zinc powder and acetone were placed in a high-speed dispersion kettle, and the dispersion rate was controlled at 6000 rpm. After intensive dispersion for 3 hours, the dispersion rate was reduced to 2000 rpm, ethyl silicate was added to the kettle, and then deionized water was added dropwise at a rate of 0.01 g / min. After the addition was completed, the dispersion reaction was continued for 2 hours, and then hexamethyldisilazane was added. After the dispersion reaction was continued for 1 hour, centrifugation was performed, and the separated solid was washed with anhydrous ethanol for 3 times, and then placed in a 50°C oven and dried for 5 hours to obtain modified zinc powder.
[0081] The zinc powder is spherical zinc powder with a particle size of 600 mesh;
[0082] The mass ratio of the zinc powder, acetone, ethyl silicate, deionized water and hexamethyldisilazane is 40:130:5:0.5:2.
[0083] Step 2: Preparation of modified conductive carbon black
[0084] Conductive carbon black and deionized water are placed in a high-speed dispersion kettle, and the dispersion rate is controlled at 7000 rpm. After 5 hours of strong dispersion, the dispersion rate is reduced to 2000 rpm, and then the temperature is increased and kept constant at 40°C, and then trifluoroacetic acid and sulfuric acid are added. After the constant temperature dispersion reaction is performed for 4 hours, centrifugation is performed, and the separated solid is washed with deionized water for 3 times, and dried at 80°C for 4 hours to obtain surface-etched conductive carbon black. Then, the surface-etched conductive carbon black and acetone are placed in a high-speed dispersion kettle, and the dispersion rate is controlled at 8000 rpm. After 6 hours of strong dispersion, the dispersion rate is reduced to 2000 rpm, and then 3-aminopropyltriethoxysilane is added. After the dispersion reaction is continued for 5 hours, centrifugation is performed, and the separated solid is washed with deionized water for 2 times, and dried at 60°C for 4 hours to obtain modified conductive carbon black.
[0085] The particle size of the conductive carbon black is 20 nm and the specific surface area is 800 m 2 / g, oil absorption is 200mL / 100g, and resistance is 0.1Ω·m;
[0086] The mass ratio of the conductive carbon black, deionized water, trifluoroacetic acid and sulfuric acid is 20:100:5:15;
[0087] The mass ratio of the conductive carbon black, acetone and 3-aminopropyltriethoxysilane for surface etching is 10:90:5.
[0088] Step 3: Preparation of component A
[0089] The specific formula of the component A is, in parts by weight:
[0090] 130 parts of potassium silicate aqueous solution,
[0091] 10 parts of carboxylated modified cellulose nanocrystal pre-dispersion liquid,
[0092] 20 parts of deionized water;
[0093] In the potassium silicate aqueous solution, the mass concentration of potassium silicate is 20wt%, and the modulus of potassium silicate is 2;
[0094] The preparation method of the carboxylated modified cellulose nanocrystal pre-dispersion liquid is as follows: after mixing the carboxylated modified cellulose nanocrystal and deionized water at a mass ratio of 17:130, using a high-speed disperser to vigorously disperse for 5 hours at a speed of 8000 rpm to obtain a gel-like viscous liquid, which is the carboxylated modified cellulose nanocrystal pre-dispersion liquid;
[0095] The carboxylated modified cellulose nanocrystals have a diameter of 4 nm, a length of 100 nm, and a surface carboxyl content of 0.4 mmol / g;
[0096] According to the specific formula of component A of the water-based inorganic zinc-rich primer that can be constructed in a low-temperature environment, in parts by weight, corresponding parts by weight of potassium silicate aqueous solution, carboxyl modified cellulose nanocrystal pre-dispersion liquid, and deionized water are put into a high-speed dispersing kettle, and the dispersion rate is controlled at 5000 rpm. After intensive dispersion for 1.5 hours, the material is discharged to obtain component A.
[0097] Step 4: Preparation of component B
[0098] The specific formula of the B component is, in parts by weight:
[0099] 80 parts of modified zinc powder,
[0100] 10 parts of modified conductive carbon black,
[0101] 3 parts of composite low temperature quick drying catalyst,
[0102] 20 parts of ferrophosphorus powder;
[0103] The composite low-temperature quick-drying catalyst is prepared by mixing 4-aminobutyric acid, pyromellitic acid and mellitic acid in a mass ratio of 1:30:5, drying in an oven at 40° C. for 13 hours, and then putting the mixture into a dry ball mill for ball milling to a particle size of 0.5 μm, and then discharging the mixture to obtain a powdered composite low-temperature quick-drying catalyst.
[0104] The particle size of the ferrophosphorus powder is 600 mesh;
[0105] According to the specific formula of component B of the water-based inorganic zinc-rich primer that can be constructed in a low-temperature environment, in parts by weight, corresponding parts by weight of modified zinc powder, modified conductive carbon black, composite low-temperature quick-drying catalyst, and ferrophosphorus powder are put into a high-speed mixer, the stirring rate is controlled at 130 rpm, and after stirring and mixing for 1 hour, the material is discharged to obtain component B.
[0106] Example 3: A method for preparing a water-based inorganic zinc-rich primer that can be applied in a low temperature environment
[0107] Step 1: Preparation of modified zinc powder
[0108] The zinc powder and acetone were placed in a high-speed dispersion kettle, and the dispersion rate was controlled at 9500 rpm. After 7 hours of strong dispersion, the dispersion rate was reduced to 3500 rpm, ethyl silicate was added to the kettle, and then deionized water was added dropwise at a rate of 0.4 g / min. After the addition was completed, the dispersion reaction was continued for 5 hours, and then hexamethyldisilazane was added. After the dispersion reaction was continued for 3.5 hours, centrifugation was performed, and the separated solid was washed with anhydrous ethanol for 4 times, and then placed in a 60°C oven and dried for 10 hours to obtain modified zinc powder;
[0109] The zinc powder is spherical zinc powder with a particle size of 1000 mesh;
[0110] The mass ratio of the zinc powder, acetone, ethyl silicate, deionized water and hexamethyldisilazane is 75:200:15:1.1:5.
[0111] Step 2: Preparation of modified conductive carbon black
[0112] Conductive carbon black and deionized water are placed in a high-speed dispersion kettle, and the dispersion rate is controlled at 10,000 rpm. After 9 hours of strong dispersion, the dispersion rate is reduced to 3,000 rpm, and then the temperature is increased and kept constant at 60°C, and then trifluoroacetic acid and sulfuric acid are added. After the constant temperature dispersion reaction is performed for 7 hours, centrifugal separation is performed, and the separated solid is washed with deionized water for 5 times, and dried at 90°C for 9 hours to obtain surface-etched conductive carbon black. Then, the surface-etched conductive carbon black and acetone are placed in a high-speed dispersion kettle, and the dispersion rate is controlled at 10,000 rpm. After 10 hours of strong dispersion, the dispersion rate is reduced to 3,500 rpm, and then 3-aminopropyltriethoxysilane is added. After the dispersion reaction is continued for 8 hours, centrifugal separation is performed, and the separated solid is washed with deionized water for 4 times, and dried at 90°C for 8 hours to obtain modified conductive carbon black.
[0113] The particle size of the conductive carbon black is 30 nm and the specific surface area is 1000 m 2 / g, oil absorption value is 300mL / 100g, and resistance is 0.5Ω·m;
[0114] The mass ratio of the conductive carbon black, deionized water, trifluoroacetic acid and sulfuric acid is 60:220:25:30;
[0115] The mass ratio of the conductive carbon black, acetone and 3-aminopropyltriethoxysilane for surface etching is 50:180:11.
[0116] Step 3: Preparation of component A
[0117] The specific formula of the component A is, in parts by weight:
[0118] 180 parts of potassium silicate aqueous solution,
[0119] 25 parts of carboxylated modified cellulose nanocrystal pre-dispersion liquid,
[0120] 55 parts of deionized water;
[0121] In the potassium silicate aqueous solution, the mass concentration of potassium silicate is 30wt%, and the modulus of potassium silicate is 3.5;
[0122] The preparation method of the carboxylated modified cellulose nanocrystal pre-dispersion liquid is as follows: after mixing the carboxylated modified cellulose nanocrystal and deionized water at a mass ratio of 29:130, using a high-speed disperser to vigorously disperse the mixture at a speed of 12,000 rpm for 9 hours to obtain a gel-like viscous liquid, namely the carboxylated modified cellulose nanocrystal pre-dispersion liquid;
[0123] The carboxylated modified cellulose nanocrystals have a diameter of 10 nm, a length of 500 nm, and a surface carboxyl content of 0.7 mmol / g;
[0124] According to the specific formula of component A of the water-based inorganic zinc-rich primer that can be constructed in a low-temperature environment, calculated in parts by weight, corresponding parts by weight of potassium silicate aqueous solution, carboxyl modified cellulose nanocrystal pre-dispersion liquid, and deionized water are put into a high-speed dispersing kettle, and the dispersion rate is controlled at 8000 rpm. After intensive dispersion for 3 hours, the material is discharged to obtain component A.
[0125] Step 4: Preparation of component B
[0126] The specific formula of the B component is, in parts by weight:
[0127] 130 parts of modified zinc powder,
[0128] 25 parts of modified conductive carbon black,
[0129] 8 parts of composite low temperature quick drying catalyst,
[0130] 45 parts of ferrophosphorus powder;
[0131] The composite low-temperature quick-drying catalyst has a preparation method comprising: mixing 4-aminobutyric acid, pyromellitic acid and mellitic acid in a mass ratio of 4:60:9, drying in an oven at 60° C. for 20 hours, and then putting the mixture into a dry ball mill for ball milling to a particle size of 3 μm, and discharging the mixture to obtain a powdered composite low-temperature quick-drying catalyst;
[0132] The particle size of the ferrophosphorus powder is 800 mesh;
[0133] According to the specific formula of component B of the water-based inorganic zinc-rich primer that can be constructed in a low-temperature environment, in parts by weight, corresponding parts by weight of modified zinc powder, modified conductive carbon black, composite low-temperature quick-drying catalyst, and ferrophosphorus powder are put into a high-speed mixer, and the stirring rate is controlled at 200 rpm. After stirring and mixing for 2.5 hours, the material is discharged to obtain component B.
[0134] Comparative Example 1: Based on Example 1, step 1, preparation of modified zinc powder, is not performed. In step 4, preparation of component B, 100 parts of modified zinc powder are replaced by 100 parts of zinc powder. The specific operation is as follows:
[0135] Step 1, preparation of modified zinc powder is not performed;
[0136] The operations of steps 2 and 3 are the same as those of Example 1;
[0137] Step 4: Preparation of component B
[0138] 100 parts of modified zinc powder were replaced by 100 parts of zinc powder, and other operations were the same as in Example 1;
[0139] The zinc powder is spherical zinc powder with a particle size of 900 meshes.
[0140] Comparative Example 2: Based on Example 1, step 2, preparation of modified conductive carbon black, is not performed. In step 4, preparation of component B, 20 parts of modified conductive carbon black are replaced by 20 parts of modified zinc powder. The specific operation is as follows:
[0141] The operation of step 1 is the same as that of embodiment 1;
[0142] Step 2, preparation of modified conductive carbon black is not performed;
[0143] The operation of step 3 is the same as that of embodiment 1;
[0144] Step 4: Preparation of component B
[0145] 20 parts of modified conductive carbon black were replaced by 20 parts of modified zinc powder, and other operations were the same as in Example 1.
[0146] Comparative Example 3: Based on Example 1, step 2, preparation of modified conductive carbon black, is not performed. In step 4, preparation of component B, 20 parts of modified conductive carbon black are replaced by 20 parts of conductive carbon black. The specific operation is as follows:
[0147] The operation of step 1 is the same as that of embodiment 1;
[0148] Step 2, preparation of modified conductive carbon black is not performed;
[0149] The operation of step 3 is the same as that of embodiment 1;
[0150] Step 4: Preparation of component B
[0151] 20 parts of modified conductive carbon black were replaced by 20 parts of conductive carbon black, and the other operations were the same as in Example 1;
[0152] The particle size of the conductive carbon black is 26 nm and the specific surface area is 950 m 2 / g, oil absorption is 240mL / 100g, and resistance is 0.2Ω•m.
[0153] Comparative Example 4: Based on Example 1, in step 4, in the preparation of component B, 5 parts of the composite low-temperature quick-drying catalyst were replaced by 5 parts of modified zinc powder in equal amounts, and the specific operation was as follows:
[0154] The operations of steps 1, 2, and 3 are the same as those of Example 1;
[0155] Step 4: Preparation of component B
[0156] 5 parts of the composite low-temperature quick-drying catalyst were replaced by 5 parts of modified zinc powder in equal amounts, and the other operations were the same as in Example 1.
[0157] Comparative Example 5: Based on Example 1, in step 3, in the preparation of component A, 20 parts of the carboxylated modified cellulose nanocrystal pre-dispersion liquid were replaced with 20 parts of potassium silicate aqueous solution in equal amounts, and the specific operation was as follows:
[0158] The operations of steps 1 and 2 are the same as those of Example 1;
[0159] Step 3: Preparation of component A
[0160] The 20 parts of carboxylated modified cellulose nanocrystal pre-dispersion liquid were replaced by 20 parts of potassium silicate aqueous solution, and the other operations were the same as in Example 1;
[0161] The operation of step 4 is the same as that of embodiment 1.
[0162] Performance Test:
[0163] Component A and component B are mixed in a mass ratio of 3:7, and component B is added to component A. After being stirred and dispersed evenly, a small amount is placed in a beaker, and the powder sedimentation in the evenly stirred primer is observed. The time taken for a 2 mm transparent layer to appear on the top layer of the primer in the beaker is recorded as the construction time. The shorter the time, the faster the powder sedimentation in the primer and the worse the construction performance. Within the construction time, the primer is sprayed into a film, and the wet film thickness is controlled to be 20-26 microns and the dry film thickness is 15-20 microns. The evaluation of the paint film performance obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4, and 5 is evaluated according to the following standards:
[0164] (1) Surface drying time and actual drying time refer to GB / T1725-2007;
[0165] (2) The flexibility of the paint film shall refer to GB / T1731-1993;
[0166] (3) Adhesion refers to GB / T5210-2006;
[0167] (4) Neutral salt spray resistance, refer to GB / T1765-1979;
[0168] (5) The high temperature resistance test method is to place the steel plate with paint film in a 400℃ environment.
[0169] Baking, record the time it takes for the paint film surface to begin to show cracks, bubbles and other damage; the above index test data are shown in Table 1:
[0170] Table 1
[0171]
[0172] From the data in Table 1, it can be seen that the construction time of Examples 1, 2, and 3 is all over 80 minutes. For spray construction, this construction window period is quite long, which is sufficient to ensure the uniform stability of the primer mixture during the construction period after the two-component primer is evenly mixed. Moreover, the surface drying time of the three embodiments at a low temperature of 5°C is within 6 minutes, and the actual drying time is also within 42 minutes. The surface drying and actual drying time at 20°C are shortened to within 4 minutes and within 26 minutes. The paint films of the three embodiments have very good flexibility, adhesion greater than 12MPa, neutral salt spray resistance of more than 5700 hours, and high temperature resistance. More than 250 hours, which shows that the water-based inorganic zinc-rich primer obtained by the present invention can be constructed in a low temperature environment, and the construction window period is long, the coating is dense without microscopic fine pores and has excellent anti-corrosion performance, and also has excellent high temperature resistance; in Comparative Example 1, the modified zinc powder is replaced by zinc powder in equal amounts, and the construction time of Comparative Example 1 is shortened. This may be because after the zinc powder is modified, the surface is coated with active silanol groups, and there is a certain hydrogen bonding effect with the aqueous solution, which can inhibit the rapid sedimentation of the zinc powder to a certain extent. The surface drying time and the actual drying time of Comparative Example 1 are drastically reduced, which shows that the surface active silanol groups of the modified zinc powder can It reacts rapidly with the hydroxyl group at the end of potassium silicate, thereby increasing the reaction rate and accelerating the drying and curing speed of the paint film. The flexibility of the paint film of Comparative Example 1 does not change, the neutral salt spray resistance performance decreases significantly, and the high temperature resistance performance also decreases relatively sharply. This shows that the surface silanol of the modified zinc powder can not only accelerate the curing rate, but also improve the cross-linking density of the paint film and the adhesion of the zinc powder to the substrate after the reaction, thereby improving the corrosion resistance and high temperature resistance. Comparative Example 2 replaces the modified conductive carbon black with modified zinc powder in equal amounts. The construction time of Comparative Example 2 is shortened to 62 minutes, which may be due to the sudden increase in the amount of zinc powder added. The spacing between zinc powders becomes smaller, and it is easy to aggregate and settle, resulting in a faster sedimentation rate. The surface drying time and the actual drying time of Example 2 are also extended. This may be because after the conductive carbon black is modified, the amino functional groups on the surface can catalyze the surface drying and actual drying of the paint film. The flexibility and adhesion of the paint film of Example 2 also decrease significantly. This may be because after the amount of zinc powder added increases, the zinc powder particles aggregate and become larger, resulting in more stress concentration in the paint film. In addition, the increase in zinc powder particles will also reduce the cross-linking density of the paint film, resulting in more microscopic gaps, so the corrosion resistance will decrease, and the high temperature resistance will also decrease.In Comparative Example 3, the modified conductive carbon black is replaced by conductive carbon black, that is, the conductive carbon black is not surface modified. The construction time of Comparative Example 3 is shortened to 74 minutes, the surface drying time and the actual drying time are significantly prolonged, the flexibility of the paint film is significantly deteriorated, and the neutral salt spray resistance and high temperature resistance are significantly reduced. This may be because the conductive carbon black is a non-polar filler. If it is not surface modified, it is difficult to be evenly dispersed in the water-based system. Excessive conductive carbon black agglomerates are easy to settle, shortening the construction window period. In addition, the excessively large agglomerates of the conductive carbon black increase the spatial distance between the reaction materials during the drying and curing process of the paint film, which also has a negative impact on the drying of the paint film. In addition, the conductive carbon black is not easily dispersed in the water-based system. Too large agglomerates of conductive carbon black will also cause stress concentration, reduce the flexibility of the paint film, and the adhesion will also decrease because the large agglomerates of conductive carbon black have no reaction activity and are not chemically bonded to the substrate, thereby affecting the salt spray resistance and high temperature resistance of the paint film; in Comparative Example 4, the composite low-temperature quick-drying catalyst is replaced with modified zinc powder. The construction time of Comparative Example 4 is basically the same as that of Example 1, which shows that the composite low-temperature quick-drying catalyst has little effect on the sedimentation of zinc powder in the primer. The surface drying time and actual drying time of Comparative Example 4 are greatly extended, which shows that the composite low-temperature quick-drying catalyst plays a very critical role in improving the curing rate of the paint film, and the neutral salt resistance of Comparative Example 4 The fog hours decreased significantly, and the high temperature resistance also decreased. This shows that the composite low-temperature quick-drying catalyst has a positive effect on improving the anti-corrosion and high-temperature resistance of the paint film. Although the composite low-temperature quick-drying catalyst is an organic matter, in theory it should have a negative impact on the corrosion resistance and high-temperature resistance of the paint film. This may be because the composite low-temperature quick-drying catalyst can greatly increase the cross-linking density of the paint film, thereby compensating for and overcompensating for the decrease in corrosion resistance and high-temperature resistance caused by organic matter; no carboxyl modified cellulose nanocrystal pre-dispersion is added to Comparative Example 5, and the construction time of Comparative Example 5 is very short, which may be due to the carboxyl modified cellulose nanocrystal pre-dispersion. The thixotropic thickening effect of the rice crystals is very good, which can prevent the rapid sedimentation of zinc powder. The surface drying time and actual drying time of comparative example 5 are also greatly increased, which shows that the carboxyl groups on the surface of the carboxylated modified cellulose nanocrystals can effectively catalyze the drying and curing reaction of the paint film and increase the drying rate. The flexibility of the paint film in comparative example 5 is poor, and the adhesion is also reduced. The neutral salt spray resistance performance is basically unchanged, and the high temperature resistance performance is improved. This shows that the carboxylated modified cellulose nanocrystals, as an organic polymer, can improve the flexibility and adhesion of the paint film, and at the same time have no obvious negative impact on the salt spray resistance of the paint film, but have a certain degree of negative impact on the high temperature resistance of the paint film. ;
[0173] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A water-based inorganic zinc-rich primer that can be applied in a low-temperature environment, characterized in that: The water-based inorganic zinc-rich primer that can be applied in a low-temperature environment is composed of two components, A and B. During application, component A and component B are evenly mixed in a mass ratio of 3 to 4:7 and then used; The specific formula of the component A is, in parts by weight: 130-180 parts of potassium silicate aqueous solution, 10-25 parts of carboxylated modified cellulose nanocrystal pre-dispersion liquid, 20~55 parts of deionized water; In the potassium silicate aqueous solution, the mass concentration of potassium silicate is 20-30wt%, and the modulus of potassium silicate is 2-3.5; The carboxyl modified cellulose nanocrystal pre-dispersion liquid is prepared by mixing the carboxyl modified cellulose nanocrystal and deionized water in a mass ratio of 17-29:130, and then strongly dispersing the mixture into a gel-like viscous liquid, i.e. the carboxyl modified cellulose nanocrystal pre-dispersion liquid; The carboxylated modified cellulose nanocrystals have a diameter of 4-10 nm, a length of 100-500 nm, and a surface carboxyl content of 0.4-0.7 mmol / g; The specific formula of the B component is, in parts by weight: Modified zinc powder 80~130 parts, Modified conductive carbon black 10~25 parts, 3~8 parts of composite low temperature quick drying catalyst, 20~45 parts of ferrophosphorus powder; The composite low-temperature quick-drying catalyst is prepared by mixing 4-aminobutyric acid, pyromellitic acid, and mellitic acid in a mass ratio of 1-4:30-60:5-9, drying, and ball-milling to obtain a powder with a particle size of 0.5-3 μm, thereby obtaining the composite low-temperature quick-drying catalyst; The particle size of the ferrophosphorus powder is 600-800 mesh; The modified zinc powder is prepared by: placing zinc powder and acetone in a high-speed dispersing kettle, vigorously dispersing them uniformly, adding ethyl silicate into the kettle, and then dripping deionized water at a rate of 0.01 to 0.4 g / min, reacting for 2 to 5 hours after the dripping is completed, then adding hexamethyldisilazane, continuing the reaction for 1 to 3.5 hours, centrifuging, washing the separated solid with anhydrous ethanol and drying, and obtaining the modified zinc powder; The modified conductive carbon black has a preparation method comprising: placing conductive carbon black and deionized water in a high-speed dispersing kettle, vigorously dispersing them uniformly, then heating them and keeping the temperature constant at 40-60°C, then adding trifluoroacetic acid and sulfuric acid, and performing a dispersion reaction at a constant temperature, then centrifuging, washing the separated solid with deionized water and drying it to obtain surface-etched conductive carbon black, then placing the surface-etched conductive carbon black and acetone in a high-speed dispersing kettle, vigorously dispersing them uniformly, then adding 3-aminopropyltriethoxysilane, and after the reaction is complete, centrifuging, washing the separated solid with deionized water and drying it to obtain the modified conductive carbon black; The particle size of the conductive carbon black is 20-30 nm, and the specific surface area is 800-1000 m 2 / g, oil absorption value is 200~300mL / 100g, and resistance is 0.1~0.5Ω·m.
2. The water-based inorganic zinc-rich primer that can be applied in a low-temperature environment according to claim 1 is characterized in that: The zinc powder is spherical zinc powder with a particle size of 600-1000 mesh; In the preparation method of the modified zinc powder, the mass ratio of zinc powder, acetone, ethyl silicate, deionized water and hexamethyldisilazane is 40-75:130-200:5-15:0.5-1.1:2-5.
3. The water-based inorganic zinc-rich primer that can be applied in a low temperature environment according to claim 1 is characterized in that: In the preparation method of the modified conductive carbon black, the mass ratio of the conductive carbon black, deionized water, trifluoroacetic acid and sulfuric acid is 20-60:100-220:5-25:15-30; The mass ratio of the conductive carbon black, acetone and 3-aminopropyltriethoxysilane for surface etching is 10-50:90-180:5-11.
4. The method for preparing a water-based inorganic zinc-rich primer that can be constructed in a low-temperature environment according to claim 1, characterized in that: The preparation of the component A is based on the specific formula of the component A of the water-based inorganic zinc-rich primer that can be applied in a low-temperature environment, in parts by weight, and the corresponding parts by weight of potassium silicate aqueous solution, carboxyl modified cellulose nanocrystal pre-dispersion liquid, and deionized water are put into a high-speed dispersion kettle, and the material is discharged after strong dispersion and uniformity to obtain the component A.
5. The method for preparing a water-based inorganic zinc-rich primer that can be applied in a low-temperature environment according to claim 1, characterized in that: The preparation of the component B is as follows: according to the specific formula of the component B of the water-based inorganic zinc-rich primer that can be applied in a low-temperature environment, in parts by weight, the corresponding parts by weight of modified zinc powder, modified conductive carbon black, composite low-temperature quick-drying catalyst, and ferrophosphorus powder are put into a high-speed mixer, stirred and mixed evenly, and then discharged to obtain the component B.
Citation Information
Patent Citations
Slow-release dry-type aqueous inorganic zinc-rich coating and preparation method thereof
CN102775828A
Corrosion-preventing aqueous inorganic zinc-rich primer as well as preparation method and application thereof
CN104974626A
Quick-drying type organic zinc-rich coating and preparation method thereof
CN103205179A
Fast-curing anticorrosion paint for inner wall of oil storage tank and preparation method thereof
CN105295619A